1978
DOI: 10.1111/j.1365-2621.1978.tb07387.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Drying on Pectin Made From Lime and Lemon Pomace

Abstract: Samples of approximately 3.50 kg of commercially leached lime and lemon peel were dried in a pilot plant direct fired rotary dryer with inlet air temperatures of 370, 425 and 535°C yielding dried pectin pomace with a final moisture content of 15-20, 8-12 and 3-7%, respectively. Pectin was extracted from laboratory leached, undried peel, each of the above dried samples, and commercially leached and dried samples. From fresh peel leached in the laboratory, we found a 65.6 and 55.9% yield of 150 grade pectin on a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

1983
1983
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 3 publications
0
14
0
Order By: Relevance
“…In addition, Crandall et al . () showed that a reduction in moisture content of the sample reduced the extraction yield of dry samples compared with fresh samples. Using dried samples in the current study may also account for the lower pectin content measured in golden kiwifruit compared with the values reported by Yuliarti et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Crandall et al . () showed that a reduction in moisture content of the sample reduced the extraction yield of dry samples compared with fresh samples. Using dried samples in the current study may also account for the lower pectin content measured in golden kiwifruit compared with the values reported by Yuliarti et al .…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Liu et al (2006) showed that the pectin yield was reduced following an increase in the ratio of sample to water and was undetected when a ratio of 1:50 was used. In addition, Crandall et al (1978) showed that a reduction in moisture content of the sample reduced the extraction yield of dry samples compared with fresh samples. Using dried samples in the current study may also account for the lower pectin content measured in golden kiwifruit compared with the values reported by Yuliarti et al (2011) for golden kiwifruit grown in New Zealand.…”
Section: Extracting Solventmentioning
confidence: 99%
“…When compared to commercial lime pectin with a color of L*91.6,a* 1.8,b* 14.6, the soy pectinaceous material was found to be slightly darker in color. Typically pectin extracted from lime or lemon peel has a yield of about 30% and a purity greater than 65% (Crandall et al 1978). The minimum 65% purity as galacturonic acid is required by USP Standards.…”
Section: Small Scale Pilot Plant Extractionsmentioning
confidence: 99%
“…This feature allows better penetration of extracting solvent into the tissues; improving the subsequent extraction of pectin. Microwave extraction also gave a higher rate and amount of extraction [14].…”
Section: Introductionmentioning
confidence: 98%